Study on the Effect of Air Throttling on Flame Stabilization of an Ethylene Fueled Scramjet Combustor. (17th September 2015) - Tian, Ye; Yang, Shunhua; Le, Jialing
Abstract : The effect of air throttling on flame stabilization of an ethylene fueled scramjet combustor was investigated by numerical simulation and experiments in this paper. The results were obtained under the inflow condition with Mach number of 2.0, total temperature of 900 K, total pressure of 0.8 MPa, and total equivalence ratio of 0.5. The shock train generated by air throttling had a big effect on the flow structure of the scramjet combustor. Compared with the combustor without air throttling, the flow field with air throttling had a lower velocity and higher pressure, temperature, and vortices intensity. Air throttling was an effective way to achieve flame stabilization; the combustion in the combustor without air throttling was nearly blowout. In the experiment, the combustion was nearly blowout with air throttling location of 745 mm, and the fuel/air mixture in the combustor with air throttling location of 875 mm was burned intensively. It was important to choose the location and time sequence of air throttling for fuel ignition and flame stabilization. The numerical simulation results agreed well with experimental measurements.